2021
DOI: 10.1002/jib.649
|View full text |Cite
|
Sign up to set email alerts
|

Identifying drivers of liking for Korean traditional rice wine ( Yakju ) across different age groups by penalty analysis based on the CATA method

Abstract: The Korean traditional rice wine, yakju, has been gaining popularity, especially among young consumers. However, research addressing the consumer acceptance of yakju, based on age, has been limited. This study aimed to identify the drivers of liking and disliking for yakju, across different age groups, by comparing the results of a penalty analysis (PA) based on the check‐all‐that‐apply (CATA) method, with those of the partial least squares (PLS) regression. Overall liking and CATA attributes of 12 commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 44 publications
(75 reference statements)
1
8
1
Order By: Relevance
“…Yang et al [65] reported that yellow-or orange-colored complexes can be formed due to the different yeast or starter used in rice wine. Low OL for product C (below 4.0, refer to Table 2) may be attributed to this strong "yellowness" However, this is not in agreement with a previous study [64] that reported that such an appearance as "yellowness" showed little or no negative impact on the OL of yakju. This inconsistency may be because a larger proportion of consumers (>80%) perceived this product as less sweet in the current study.…”
Section: Penalty Analysis (Pa) Of Cata-jar Methodscontrasting
confidence: 65%
See 1 more Smart Citation
“…Yang et al [65] reported that yellow-or orange-colored complexes can be formed due to the different yeast or starter used in rice wine. Low OL for product C (below 4.0, refer to Table 2) may be attributed to this strong "yellowness" However, this is not in agreement with a previous study [64] that reported that such an appearance as "yellowness" showed little or no negative impact on the OL of yakju. This inconsistency may be because a larger proportion of consumers (>80%) perceived this product as less sweet in the current study.…”
Section: Penalty Analysis (Pa) Of Cata-jar Methodscontrasting
confidence: 65%
“…PA is a useful tool to analyze the potential penalty paid by the product regarding reduced OL for not being "just about right" on an attribute, and the penalty is often called the mean drop in OL [64]. PA with data from CATA questions was introduced based on the ideal profile concept [24,29].…”
Section: Penalty Analysis (Pa) Of Cata-jar Methodsmentioning
confidence: 99%
“…PLS regression was also conducted using PS and CATA results, attributes (matrix X : independent variable), and hedonic mean (matrix Y : dependent variable) (Lee et al, 2021) to filter the most significant attributes to predict the sensory drivers of liking.…”
Section: Methodsmentioning
confidence: 99%
“…Sensory drivers of liking are the attributes with the most relevant positive effects on general taste, aroma, appearance, and texture (Kuesten & Bi, 2018; Lee et al, 2021). Like this, the sensory drivers of liking are the sensory attributes that drive product acceptance (Moskowitz, 2002; Rocha et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation